GaMa Feedback Learning Model: Basic Concept and Design - Purbohadi, Dwijoko (2013)
Ideally, in teaching and learning activity, there should be one teacher for one student, supported by sufficient instruments, and appropriate methods. Currently, a teacher assists a number of students. Teachers have limited time to monitor and help a student overcome their learning problems. This paper proposes a mastery learning model using e-learning that applies control mechanism to solve above problems. The model is applied in group learning, but the actual target is individual learning. Teachers have plenty of time to supervise, evaluate, and take necessary actions when finding a student with learning problems. The principles of control mechanism can be operated if it is already equipped with Learning Management System (LMS), in which it has been enriched with Intelligent Tutoring System (ITS) and appropriate instructional. The students will be more autonomous and the teachers serve more as monitors and assistants to promote a bigger number of students who can achieve mastery.